DESAIN DAN IMPLEMENTASI ANTARMUKA SISTEM BACKOFFICE BERBASIS WEB DENGAN DASHBOARD ROLE-BASED MENGGUNAKAN MODEL PROTOTYPE - Rahma Khamila, Alya; Voutama, Apriade (STMIK KAPUTAMA, 2026)
A backoffice system is an internal information system used to support various operational activities within an organization. It plays an important role in managing users, monitoring system activities, recording audit logs, and presenting administrative information in a structured manner. Company X requires a web-based backoffice interface that can provide dashboards according to user roles and support several essential modules such as authentication, user management, and operational monitoring. Currently, the company does not yet have a consistent and responsive backoffice interface, which causes administrative tasks and system monitoring to be less efficient. This study aims to design and develop a web-based backoffice interface that is modular, reusable, and easier to maintain based on the identified functional requirements. The research applies a software engineering approach using the System Development Life Cycle (SDLC) with the Prototype model. The development process includes requirement analysis, interface design, implementation using Next.js and React, integration with a dummy backend through REST APIs, and functional testing of the Prototype. The result of this research is a backoffice interface Prototype that includes a login page, navigation structure, role-based dashboard, User Management module, reusable UI components, and interactive data visualization. The developed interface provides a structured system layout and can support more efficient administrative and monitoring activities.